2016
DOI: 10.3329/rujse.v44i0.30361
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Aluminium-Rice Husk Ash Composite Prepared by Stir Casting Method

Abstract: Metal Matrix Composites (MMCs) constitute an important category of design and weightefficient materials. This article highlights on the work where an attempt is taken to fabricate aluminium matrix composite reinforced with rice husk ash (RHA) particles, an agricultural byproduct with high amount of silica. RHA particles, upon analysis, are incorporated into the Al matrix melt by stir casting. Magnesium (~1%) is used as a wetting agent between matrix and reinforcement. 3, 6 and 9% wt. of RHA are added into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Compo-cast AA6061 alloy based composites reinforced with rice husk ash particles showed that due to (i) uniform distribution (ii) good interfacial bonding and (iii) absence of interfacial reaction products, the addition of up to 8% rice husk ash particles (2-3 µm) improved the strength and hardness [49]. In another study, the use of Mg (1%) as a wetting agent ensured good interfacial bonding between the rice husk ash particle (105-420 µm) reinforcement and Al-matrix, along with uniform distribution, resulting in increased hardness and strength of the composite (Table 21) [50]. The properties of stir cast Al-Mg-Si matrix composites reinforced with (2 to 6 wt.%) rice husk ash particles and 10 wt.…”
Section: Rice Husk Ash Reinforced Metal Matrix Compositesmentioning
confidence: 95%
“…Compo-cast AA6061 alloy based composites reinforced with rice husk ash particles showed that due to (i) uniform distribution (ii) good interfacial bonding and (iii) absence of interfacial reaction products, the addition of up to 8% rice husk ash particles (2-3 µm) improved the strength and hardness [49]. In another study, the use of Mg (1%) as a wetting agent ensured good interfacial bonding between the rice husk ash particle (105-420 µm) reinforcement and Al-matrix, along with uniform distribution, resulting in increased hardness and strength of the composite (Table 21) [50]. The properties of stir cast Al-Mg-Si matrix composites reinforced with (2 to 6 wt.%) rice husk ash particles and 10 wt.…”
Section: Rice Husk Ash Reinforced Metal Matrix Compositesmentioning
confidence: 95%
“…RHA can be used to reduce greenhouse gas emissions because trees ingest CO 2 as they develop, and this carbon is released when renewable energy from animals and plants is burned. In [17,18], the synthesis and mechanical characteristics of aluminium reinforced composites with RHA were investigated by the stir casting method. Mechanical testing was performed on both the monolithic metal alloy and the composite material.…”
Section: Rick Husk Ash (Rha)mentioning
confidence: 99%
“…Many researchers studied the influence of these agrowaste reinforcements on the mechanical properties of Al based composites. Ahamed et al [96] observed the decrease in densities of Al composites reinforced with RHA fabricated by stir casting technique;…”
Section: Mechanical Properties Of Agro-waste Reinforced Compositesmentioning
confidence: 99%